ChemInform Abstract: Bioinspired Synthesis of ZnS Supraparticles Toward Photoinduced Dechlorination of 2, 2′, 4, 4′, 5, 5′‐Hexachlorobiphenyl. Issue 44 (14th October 2013) - He, Liangcan; Xiong, Yansong; Zhao, Meiting; Mao, Xiang; Liu, Yaling; Zhao, Huijun; Tang, Zhiyong
Abstract ZnS supraparticles are prepared from aqueous solutions of Zn(ClO4)2, L‐cysteine, and NaOH (37 °C, 4 weeks).